Toll-like Receptor 7 Contributes to Inflammation, Organ Injury, and Mortality in Murine Sepsis. (July 2019) - Jian, Wenling; Gu, Lili; Williams, Brittney; Feng, Yan; Chao, Wei; Zou, Lin
Editor's Perspective: What We Already Know about This Topic: Toll-like receptor 7 responds to elevated single-stranded RNA by increasing cytokine production. Sepsis is characterized by elevated plasma levels of tissue damage (and pathogen)–associated molecular patterns, including RNA. What This Article Tells Us That Is New: Using murine models of bacterial sepsis, knockout of the Toll-like receptor 7 resulted in lower mortality and cytokine levels and less end-organ injury. Therefore, Toll-like receptor 7, which mediates innate immune response, contributes to harm in experimental sepsis. Background: Sepsis remains a critical illness with high mortality. The authors have recently reported that mouse plasma RNA concentrations are markedly increased during sepsis and closely associated with its severity. Toll-like receptor 7, originally identified as the sensor for single-stranded RNA virus, also mediates host extracellular RNA-induced innate immune responses in vitro and in vivo . Here, the authors hypothesize that innate immune signaling via Toll-like receptor 7 contributes to inflammatory response, organ injury, and mortality during polymicrobial sepsis. Methods: Sepsis was created by (1) cecal ligation and puncture or (2) stool slurry peritoneal injection. Wild-type and Toll-like receptor 7 knockout mice, both in C57BL/6J background, were used. The following endpoints were measured: mortality, acute kidney injury biomarkers, plasma and peritoneal cytokines, blood bacterial loading, peritoneal leukocyte counts, and neutrophil phagocytic function. Results: The 11-day overall mortality was 81% in wild-type mice and 48% in Toll-like receptor 7 knockout mice after cecal ligation and puncture (N = 27 per group, P = 0.0031). Compared with wild-type septic mice, Toll-like receptor 7 knockout septic mice also had lower sepsis severity, attenuated plasma cytokine storm (wild-type vs. Toll-like receptor 7 knockout, interleukin-6: 43.2 [24.5, 162.7] vs. 4.4 [3.1, 12.0] ng/ml, P = 0.003) and peritoneal inflammation, alleviated acute kidney injury (wild-type vs. Toll-like receptor 7 knockout, neutrophil gelatinase-associated lipocalin: 307 ± 184 vs. 139 ± 41-fold, P = 0.0364; kidney injury molecule-1: 40 [16, 49] vs. 13 [4, 223]-fold, P = 0.0704), lower bacterial loading, and enhanced leukocyte peritoneal recruitment and phagocytic activities at 24 h. Moreover, stool slurry from wild-type and Toll-like receptor 7 knockout mice resulted in similar level of sepsis severity, peritoneal cytokines, and leukocyte recruitment in wild-type animals after peritoneal injection. Conclusions: Toll-like receptor 7 plays an important role in the pathogenesis of polymicrobial sepsis by mediating host innate immune responses and contributes to acute kidney injury and mortality. Abstract : Using murine models of bacterial sepsis, knockout of the Toll-like receptor 7 resulted in lower mortality and cytokine levels and less end-organ injury. Therefore, Toll-like receptor 7, which mediates innate immune response, contributes to harm in experimental sepsis.Supplemental Digital Content is available in the text.